2016
DOI: 10.1016/j.infsof.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Business process maturity models: A systematic literature review

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
187
0
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(216 citation statements)
references
References 22 publications
7
187
0
22
Order By: Relevance
“…According to Wendler [2], empirical studies predominate in MMs literature. In business process management, the same conclusion was reached by Tarhan et al [47].…”
Section: Phase 1-problem Formulation and Question Identificationsupporting
confidence: 74%
See 1 more Smart Citation
“…According to Wendler [2], empirical studies predominate in MMs literature. In business process management, the same conclusion was reached by Tarhan et al [47].…”
Section: Phase 1-problem Formulation and Question Identificationsupporting
confidence: 74%
“…Carvalho et al [46] identified 14 MMs for information systems and technologies (IST) management in healthcare. Tarhan et al [47] (2016) sought an overall understanding of the existence, characteristics, and use of MMs in business process management; in a sample of 61 studies, they identify 20 business process MMs. …”
Section: Phase 1-problem Formulation and Question Identificationmentioning
confidence: 99%
“…The fundamental activity of process improvement is prioritization (which process to be improved first) (Burlton, 2010).The maturity level of processes and BPM is often considered as an indicator of improvement. However, the models lack applicability and configurability to practitioners (Röglinger et al, 2012), and most of the maturity models lack validation of empirical evidences (Tarhan et al, 2016). Previous research has introduced a few methods specifically for the purpose of prioritizing process improvement initiatives, for example, the business value scoring method (Bandara et al, 2010), the process performance scoring method (Huxley, 2003) and the value matrix of process and strategy alignment (Burlton, 2010).…”
Section: 2mentioning
confidence: 99%
“…In the first, exploratory phase, the analysis was focused on relatively recent publications undertaking comprehensive reviews on the mentioned domains, aiming at the identification of the main components (topics) of their actual conceptual frameworks. Among these recent publications with a comprehensive coverage of the knowledge for the IMS field, References [12][13][14][15] are mentioned here, and Maturity Models (MMs) [16,17], to which a publication can be added [18], are listed as a common reference for both domains. The examination of the mentioned publications allowed for the structuring of the literature review in the two domains and the formulation of the questions to which this paper should answer.…”
Section: The Review Of the Scientific Literaturementioning
confidence: 99%